Assessment of E?ect of Nasal Oxygen Supplementation During Apnoea of Intubation on Arterial Oxygen Levels - Nisha Thomas (Asian Journal of Medical Research, 2021)
Background: The aim is to evaluate the effect of nasal oxygen supplementation during apnoea of intubation on arterial oxygen levels. Subjects and Methods : A sum total of seventy patients with American Society of Anesthesiologists physical status Grade I or II in age range of        18- 40 years of either gender scheduled for surgery requiring general anaesthesia were divided into group of 2 each containing 35 patients.      In group I patients, nasal oxygen supplementation was administered at 10 L/min during apnoea of laryngoscopy and in group II, no oxygen supplementation was done. Results: The mean age was 32.5 years in group I and 31.4 years in group II, height was 164.2 cm in group I and 162.5 cm in group II, weight was 58.4 kgs in group I and 57.5 kgs in group II and BMI was 22.3 Kg/m2 in group I and 25.1 Kg/m2 in group II. pH at baseline was 7.42 and 7.40, after pre- oxygenation was 7.39 and 7.37 and after intubation was 7.30 and 7.29. PaO2 at baseline was 105.6 and 100.2, after pre- oxygenation was 342.8 and 328.4 and after intubation was 240.6 and 238.2. PaCO2 at baseline was 32.5 and 33.5, after pre- oxygenation was 35.4 and 37.2 and after intubation was 43.2 and 46.1. HCO3 at baseline was 20.4 and 21.3, after pre- oxygenation was 21.3 and 21.8 and after intubation was 22.9 and 23.7 in group I and II respectively. Desaturation safety time was 420.5 seconds in group I and 380.2 seconds in group II, resaturation time was 32.4 seconds in group I and 42.8 seconds in group II, PaO2 after intubation was 243.2 in group I and 241.9 in group II and PaCO2 after intubation was 42.7 in group I and 45.3 in group II. A non- significant difference was observed (P> 0.05). Conclusion: Apnoeic oxygen supplementation at 10 L/min flow by nasal prong did not prolong the apnoea desaturation safety periods or the PaO2.